Sacroiliac Joint Hydatidosis Mimicking Ankylosing Spondylitis: A Case Report - Sami KÜÇÜKŞEN,; Burkay Kutluhan KAÇIRA,; Sinan BAĞCACI,; İlknur ALBAYRAK,; Ozan YAŞAR1, (Archives of Rheumatology, 2014)
Hydatid cyst disease caused by Echinococcus granulosus is common in Mediterranean sheep-raising countries. Spinal involvement in hydatid cyst cases is very rare. The disease mainly affects the lungs and liver and, to a lesser extent, the brain and bones. Depending on location, the disease may mimic soft tissue and bone tumors. Osteolytic and inflammatory changes may imitate osteomyelitis and malignancies or rheumatologic diseases of the affected area. In this article, we report an unusual case of hydatid disease of the sacroiliac joint who was misdiagnosed with ankylosing spondilitis and under follow-up for two years. We also discuss the differential diagnosis of mass lesions of the sacroiliac joint. Hydatid cysts should be considered in the differential diagnosis in patients living in endemic countries.